THE INFLUENCE OF CUSTOMS AND LOGISTICS SERVICE EFFICIENCY ON CARGO DELIVERY TIME - Luzhanska, Nataliia; Lebid, Iryna; Kotsiuk, Oleksandr; Kravchenya, Irina; Demchenko, Yevhen (Proceedings of National Aviation University (archive), 2019)
The formation of a logistics chain with the use of a freight customs complex for customs and logistics service provision requires detailed research and investigation into technical, technological and organizational constraints that may affect overall cargo delivery time. Actors in the transport market, while interacting with customs authorities, have to take into account customs legislation requirements and road transport complex operational characteristics, since non-compliance with them will cause a number of delays due to the need for corrective actions and will also entail a number of penalties. In order to increase the accuracy of delivery time planning, it is considered the procedure for customs and logistics service provision involved in cargo export and import as well as for stowing cargo in a customs warehouse or a temporary storage warehouse. It is also addressed the issue of comprehensive service provision to entities engaged in foreign economic activities using a freight customs complex. The most widespread violations requiring additional correction time are identified. It is considered the technological constraints connected with the handling capacity of the research object. The influence of the organization and planning of a freight customs complex`s operation on its efficiency is determined. It is proposed to consider the lack of available resources provided by customs infrastructure facilities and the excessive idle time of vehicles as a factor in delivery time planning The paper findings can be implemented in the operation of freight customs complexes in cooperation with private sector enterprises and state organizations when performing foreign trade operations.